Extraction purification and characterization of galactomannan from fenugreek for industrial utilization. (15th January 2018) - Rashid, Farhat; Hussain, Sarfraz; Ahmed, Zaheer
Highlights: Galactomannan from local fenugreek was extracted & purified. Preliminary characterized by using proximate & mineral analysis & FTIR. Water, oil-holding, foaming capacity, swelling index, emulsion & foaming stability. Thermal stability by TGA & DSC, topography by SEM, & size distribution by XRD. Galactomannan attributes depicted a very good candidacy for industrial application. Abstract: Galactomannan, a water-soluble heteropolysaccharide was isolated and purified from seed of fenugreek locally called as Kasuri Methi. Polysaccharide was chemically characterized and its functional attributes were studied in detail. FTIR analysis divulges representative peaks of polysaccharide in region of 3324, 2914 & 1653 cm −1 . Galactomannan depicted lower water holding capacity compared to guar gum. Emulsifying activity and emulsion stability of biopolymer was on higher side as compare to reference material. Oil-holding capacity, foaming capacity, swelling index and foaming stability of galactomannan were 626.46%, 25.5%, 86%, 18.55 respectively which were higher than reference gums. Thermal analysis revealed a melting range of 66–139 °C and degradation temperature of 296.45 °C. XRD depicted a large degree of crystallinity in galactomannan. SEM imaging depicted a glittering surface which is suitable for film making. EDS spectroscopy depicted that element was not uniformly distributed in biopolymer.